Pakistan at seventy : a handbook on developments in economics, politics and society - Burki, Shahid Javed; Chowdhury, Iftekhar Ahmed (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"This handbook examines Pakistan's 70-year history from a number of different perspectives"--
An overview / Shahid Javed Burki -- The Pakistan story / Shahid Javed Burki -- Unintended consequences : the long shadow of partition on Pakistan and India / Subrata K. Mitra -- Evolution of politics / Shirin Tahir-Kheli -- Islam, society and politics in Pakistan / Riaz Hassan -- Sustained political progress : the supportive role of the military / Jehangir Karamat -- Media in Pakistan : idiom, ideology and the army / Khaled Ahmed -- Pakistan, power-play and a new South Asian paradigm / Iftekhar Ahmed Chowdhury -- Making of foreign policy : changing parameters / Aziz Ahmad Khan -- Taking stock : Pakistan-India relations / Khurshid Kasuri -- Living in a rapidly changing world / Shahid Javed Burki -- Defenders of the crescent : Pakistan-Saudi Arabia relations / Farah Jan -- Adversarial peace : India-Pakistan nuclear rivalry / Farah Jan -- A potential game changer : the China Pakistan economic corridor / Daud Ahmad -- Macroeconomic achievements and challenges / Masood Ahmed -- History of the development discourse in Pakistan / Asad Ejaz Butt -- Recent economic developments and prospects / Farrukh Iqbal -- Economic governance / Ishrat Husain -- Praetorian bureaucratization of political system and politicization of bureaucracy / Shahid Najam -- Getting technology to work for social development / Ayub Ghauri -- Akhwuat : new microcredit stories / Muhammad Saleem Ahmad Ranjha -- Private sector in education / Shahid Kardar -- Educating and employing women / Nasreen Kasuri -- The downward spiral of quality-of-life in Pakistan : is control possible, or even desired? / Kulsum Ahmed -- Water problems and solutions / Mahmood Ahmad -- Ways for solving the energy problem -- Ziad Alahdad -- The last word / Shahid Javed Burki -- Postscript / Shahid Javed Burki and Asad Ejaz Butt.
OCLC-licensed vendor bibliographic record.
Keywords: Pakistan -- History; HISTORY / Asia / India & South Asia; POLITICAL SCIENCE / Economic Conditions; POLITICAL SCIENCE / Government / General